PROSES PERUBAHAN AKTA PENDIRIAN CV KARENA PENGUNDURAN DIRI SEKUTU KOMANDITER - , RICO RODIAZ IRFANA; , Rizky Septiana W, S.H., M.Kn. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report titled Process Changes Due CV Deed of Resignation Allied Commanditaire in order to determine the formation process of the CV so I can apply in the lives of people around who need help in the establishment of CV and can figure out what the obstacles faced. Notary and PPAT is a legal profession which both of profession create an authentic deed of, but the internship has two purpose. Subjective purpose and objective purpose. The subjective purpose is to authority and obligations vary. While the process of forming the CV it self is the authority of the notary. The differences dependon their authority and obligation subjective purpose of field internship is one of the prerequisite course author can earn the title of Associate Member of the Law of Legal studies 3 Diploma Vacational School of Gadjah Mada University while the objective purpose the purpose of obyektif so the author can understand in compeherensif, the correlation between theory and practice of the law, which eventually also help author in the world of work. Benefit of field internship for author to embed direct knowledge gained during lectures and compare with the statement found in the field to add insight and knowledge to prepare themselves both theoretical as well as practical, and gain experience and training in the face of a problem in employment up, increase the ability to analyze problems in a scientific, practical, and increased vision to think.